HUBUNGAN ANTARA INTENSITAS BERMAIN GAME ONLINE DENGAN KEJADIAN INSOMNIA DAN STRES PADA MAHASISWA FAKULTAS TEKNIK DI UNIVERSITAS KADIRI TAHUN 2019 - Ula, wiwit Ruhailatul; nr, kun ika; yunalia, endang mei (Universitas Kadiri, 2019)
Correlation between the intensity of playing online games with insomnia incidence and stress in the Faculty of Engineering students at the University of Kadiri in 2019.Insomnia is a difficulty starting to maintain sleep, while stress is a feeling of tension and pressure. Most of the Faculty of Engineering students at the University of Kadiri play online games until they forget their time so they have an impact on insomnia and stress. This study is aiming to find out the correlation between playing online games with insomnia incidence and stress in the Engineering Faculty students at the University of Kadiri in 2019. This study included correlational analytic research with a cross sectional approach. The population of this study was the 5th semester students of the Faculty of Engineering at Kadiri University with a total of 56 with a sample of 48 students. The sampling technique using the simple random sampling method. Data analysis techniques use the spearman rank test with sig α = 0.05. Based on the results of the spearman rank test on variable relationship intensity of playing online games with the incidence of insomnia obtained p-value 0,000 and the correlation coefficient of r = 0.771 can be concluded Ho rejected H1 accepted, that means there is a correlation between playing online game with insomnia incidence in the Faculty of Engineering students at the University of Kadiri in 2019. With the intensity of a strong correlation and the results of the spearman rank test on the correlation variable intensity of playing online games with the occurrence of stress, obtained p-value 0,000 smaller than α = 0.05 and correlation coeffitien of r = 0.811 can be concluded Ho rejected H1 accepted, that means there is a correlation between playing online games with stressful incidence among students of the Faculty of Engineering at the University of Kadiri in 2019 with a very strong correlation strength. The higher the intensity of playing online games, the higher the incidence of insomnia and stress experienced. It is recommended for students to be able to control the durration of playing online games so as not to experience addiction which can cause students to go through the incidence of insomnia and stress. Keywords: intensity of playing online game, insomnia, stress, students.